A Qualitative Study on Representations of Intellectual and Relational Capital Among a Group of Managers in an Italian Trade-Union - Ripamonti, Silvio Carlo; Galuppo, Laura; Petrilli, Sara; Benozzo, Angelo (Frontiers in Psychology, 2021)
In this article, we present a study in which we analyzed the metaphors used by the top management of an Italian trade-union to narrate the changes that the organization was undergoing. The hypothesis underlying this study is that the interpretation of metaphors is the key to understanding both the ideas of organization most commonly held among organizational actors and their perception of two intangible assets (intellectual capital and relational capital). In the results, we illustrate the three root metaphors the union seen as a system of domination, an organism, and as a culture together with the consequences of each of these images as regards the perception and value attributed to the two intangible assets.